2014
DOI: 10.1002/anie.201409767
|View full text |Cite
|
Sign up to set email alerts
|

An Organic Molecule with Asymmetric Structure Exhibiting Aggregation‐Induced Emission, Delayed Fluorescence, and Mechanoluminescence

Abstract: Compounds displaying delayed fluorescence (DF), from severe concentration quenching, have limited applications as nondoped organic light-emitting diodes and material sciences. As a nondoped fluorescent emitter, aggregation-induced emission (AIE) materials show high emission efficiency in their aggregated states. Reported herein is an AIE-active, DF compound in which the molecular interaction is modulated, thereby promoting triplet harvesting in the solid state with a high photoluminescence quantum yield of 93.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
195
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(205 citation statements)
references
References 39 publications
5
195
3
2
Order By: Relevance
“…[12] However, much different ML behaviors appeared if the mechanical stimulus continued. [12] However, much different ML behaviors appeared if the mechanical stimulus continued.…”
mentioning
confidence: 99%
“…[12] However, much different ML behaviors appeared if the mechanical stimulus continued. [12] However, much different ML behaviors appeared if the mechanical stimulus continued.…”
mentioning
confidence: 99%
“…[37] As the luminescence of AIE-active materials is not quenched, but is enhanced in the solid state,i ti se xpected that many AIE- [38] Thed issymmetrical structure of the molecules facilitates its crystallization in anoncentrosymmetric space group,which is essential to achieve TL properties.I n2 015, Xu et al also found that molecules such as 5-[4-(1,2,2-triphenylvinyl)phenyl]thiophene-2-carbaldehyde (P4TA)s how remarkable TL properties (Figure 9). [37] As the luminescence of AIE-active materials is not quenched, but is enhanced in the solid state,i ti se xpected that many AIE- [38] Thed issymmetrical structure of the molecules facilitates its crystallization in anoncentrosymmetric space group,which is essential to achieve TL properties.I n2 015, Xu et al also found that molecules such as 5-[4-(1,2,2-triphenylvinyl)phenyl]thiophene-2-carbaldehyde (P4TA)s how remarkable TL properties (Figure 9).…”
Section: Triboluminescence In Aie-active Materialsmentioning
confidence: 99%
“…The results suggest that the origin of the PL emission enhancement of CDPA is TADF, which presented different temperature dependence degrees. [47] Fig In order to clarify why the DF emission of CDPA were observed, quantum chemical calculations for S 0 states were carried out using density functional theory (DFT) at the B3LYP/6-31G(d) level. Fig.12 shows the optimized structure and the HOMO and LUMO of CDPA.…”
Section: Self-assembly Propertymentioning
confidence: 99%
“…[12][13][14] Such abnormal fluorescent behaviour is ascribed to the restriction of internal rotations (RIR) as well as aggregation inducedplanarization and formation of J-aggregates in some cases. [15][16][17][18] AIE materials have received increasing attentions in recent years and successfully applied for sensing and bioimaging [19][20][21][22][23][24][25], OLEDs [26] and optical waveguides. [27] The results reveal that these AIE luminogens are not only strongly emissive in the solid states, but also responsive to external stimuli such as grinding and chemical vapour.…”
Section: Introductionmentioning
confidence: 99%